2011
DOI: 10.1029/2010wr009109
|View full text |Cite
|
Sign up to set email alerts
|

Historical summer base flow and stormflow trends for New England rivers

Abstract: River base flow is important to aquatic ecosystems, particularly because of its influence on summer water temperatures. Summer (June through September) daily mean streamflows were separated into base flow and stormflow components by use of an automated method at 25 stations in the New England region of the United States that drain predominantly natural basins. Summer monthly mean base flows increased from 1950–2006 at most stations in western New England with many large increases (>20%) and some very large inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 49 publications
6
74
0
Order By: Relevance
“…The pattern of increasing low flows in the northeast is consistent with regional-scale studies (e.g., Hodgkins and Dudley, 2011) and is consistent with the increases in 7-day low flows and fall precipitation shown in Small et al (2006) that focused on a smaller set of sites across the eastern US from the HCDN. Several other studies (e.g., Douglas et al, 2000;McCabe and Wolock, 2002;Hayhoe et al, 2007;Andreadis and Lettenmaier, 2006) have identified an overall increasing trend in precipitation over the past 50 years, and a decreasing pattern in soil moisture drought over the much of the US including the northeast (Andreadis and Lettenmaier, 2006).…”
Section: Potential Drivers Of Trends In Low Flowssupporting
confidence: 72%
See 1 more Smart Citation
“…The pattern of increasing low flows in the northeast is consistent with regional-scale studies (e.g., Hodgkins and Dudley, 2011) and is consistent with the increases in 7-day low flows and fall precipitation shown in Small et al (2006) that focused on a smaller set of sites across the eastern US from the HCDN. Several other studies (e.g., Douglas et al, 2000;McCabe and Wolock, 2002;Hayhoe et al, 2007;Andreadis and Lettenmaier, 2006) have identified an overall increasing trend in precipitation over the past 50 years, and a decreasing pattern in soil moisture drought over the much of the US including the northeast (Andreadis and Lettenmaier, 2006).…”
Section: Potential Drivers Of Trends In Low Flowssupporting
confidence: 72%
“…Increases in evaporation (Walter et al, 2004;Huntington and Billmire, 2014) may have also led to declines in groundwater recharge and streamflow (Hodgkins and Dudley, 2011), and potentially cancelled out the overall increases in precipitation across much of the US (Andreadis and Lettenmaier, 2006). Figure 10 also shows an estimate of the trend in late summer/early fall potential evaporation based on the NLDAS2 data set of Xia et al (2012).…”
Section: Potential Drivers Of Trends In Low Flowsmentioning
confidence: 99%
“…Increases in summer streamflows may be attributable to increases in summer precipitation for this region, as reported by Hodgkins and Dudley (2011). In addition, increases in summer streamflows may be attributable to increased urbanization in some of these basins, which includes increases in wastewater discharge, impervious cover, and streamflow regulation.…”
Section: Changes In Streamflow Water Years 1974-2013 and 2001-13mentioning
confidence: 80%
“…The slightly increasing flow-normalized concentrations and loads of DSi may be affected by declining TP concentrations in some of the basins upstream from the monitoring sites, limiting productivity of diatoms. Observed increases in summer base flows (Hodgkins and Dudley, 2011) may be related to increasing DSi loads from groundwater.…”
Section: Silicamentioning
confidence: 99%
“…These changes have not been distributed uniformly in time or space, and snowfall and base flow have marginally decreased or increased in some places in response to local conditions. Similarly, for the 57-year study from 1950 to 2006, Hodgkins and Dudley (2011) found increased base flow and stormflow in New England, and Dudley and Hodgkins (2013) found increased groundwater levels. Hamilton and others (2010) reported on climate trends in New Hampshire; air temperature and precipitation increased throughout the 20th century, accelerating since 1970.…”
Section: Previous Investigationsmentioning
confidence: 99%